Konsep Filsafat Barat dan Islam Tentang Sumber Pengetahuan (Perspektif Rene Descartes, John Locke, dan Al-Ghazali): Western and Islamic Philosophical Concepts Regarding Sources of Knowledge (Perspectives of Rene Descartes, John Locke, and Al-Ghazali) - Anshari, Muhammad Isa (Jurnal Filsafat Indonesia, 2024)
In history there has been an important debate between Western philosophy and Islamic philosophies. This debate concerns the source of human knowledge, whether the role of reason, sensory perception, or intuition is emphasized in the process of attaining true knowledge. This research involves the views of Al-Ghazali, Rene Descartes, and John Locke, this research uses the method of literature study. In the context of this debate, the Western view of epistemology represented by Rene Descartes saw the human mind as a source of knowledge and formulated a method known as the method of the question method, while John Locke, on the other hand, highlighted the role of human senses as a resource for knowledge and elaborated the theory of tables of senses. In the midst of this Western view, Al-Ghazali presents an Islamic perspective by emphasizing the role of intuition or heart in achieving the highest knowledge. In this article, we will look at the thinking and comparison of the perspective of three figures namely Al-Ghazali, Rene Descartes, and John Locke. Each of them has a different view of the true source of knowledge.